Keamanan siber sebagai fondasi pengembangan aplikasi keuangan mobile: Studi literatur mengenai cybercrime dan mitigasinya - Shofie Azizah; Zava Nurruzzuhrotil Ula; Dwi Mutiara; Michelle Prajna Prameswari (Akuntansi dan Teknologi Informasi, 2024)
This study examines the importance of cybersecurity in mobile financial applications, particularly in the face of rising cybercrime threats. The aim of this research is to provide deeper insights into the significance of cybersecurity in mobile financial apps and to develop approaches that financial companies can adopt to protect their users' data and information. The research employs a qualitative descriptive method using a systematic literature review (SLR) approach. Meta-synthesis analysis is applied to synthesize data from 26 journal articles published between 2019 and 2024. The findings reveal that cybercrime in the financial and FinTech industries is driven by internal factors such as weak security systems, lack of system updates, limited human resource competencies, and careless user behavior. External factors include malware attacks, unclear regulations, and the use of advanced technology. To counter these, it is necessary to implement technologies such as firewalls and blockchain, strong risk management, enhanced network infrastructure, the establishment of cybersecurity teams, the development of clear regulations, and user education to raise awareness and improve cybersecurity. Therefore, the implementation of a comprehensive cybersecurity strategy is crucial in maintaining the integrity and trust of users in mobile financial applications.